Pengaruh Penggunaan E-Wallet Terhadap Perilaku Pengelolaan Keuangan Mahasiswa Generasi Gen Z - Clara Dinda Christina; Aris Eddy; Sinta Putriana (Indo Publishing, 2026)
This study aims to examine the impact of digital wallet usage on the financial habits of Generation Z. The independent variables tested include economic value, ease of use, social influence, corporate reputation, promotion, features, curiosity, and reward. A quantitative approach was applied utilizing a purposive sampling technique, with questionnaires distributed to 100 Generation Z respondents. The regression analysis results indicate that, simultaneously, all independent variables exert a significant influence on financial behavior. However, partially, only a few variables, such as promotion and reward, are proven to have a significant effect. This study concludes that positive e-wallet usage can foster more controlled and prudent financial behavior among Generation Z, while also providing implications for the development of digital financial literacy.